Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.4081/mi.2016.6302
|View full text |Cite
|
Sign up to set email alerts
|

The quality of life in girls with Rett syndrome

Abstract: Nowadays, quality of life is receiving an increasing attention in all scientific areas. Rett syndrome (RTT) is a rare neurological development, affecting mainly females. The congenital disease affects the central nervous system, and is one of the most common causes of severe intellectual disability. The aim of our study is to evaluate the effect of RTT on the quality of life of people who are affected. Both parents of 18 subjects, all female, diagnosed with RTT, took part in the research. Quality of life was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 20 publications
0
12
0
1
Order By: Relevance
“…Additional characteristic features include postnatal deceleration of head growth, motor abnormalities, gait posture ataxia, breathing dysfunction, with seizures and breathing disturbances being the most detrimental clinical phenotype in RTT (Smeets et al, 2012 ). Recent studies have evaluated the QOL in subjects with RTT and their caregivers using questionnaires such as the Italian version of the impact of childhood illness scale (Parisi et al, 2016 ). These studies have demonstrated a significant negative impact on both the child’s development and the entire family.…”
Section: Appendix Amentioning
confidence: 99%
See 1 more Smart Citation
“…Additional characteristic features include postnatal deceleration of head growth, motor abnormalities, gait posture ataxia, breathing dysfunction, with seizures and breathing disturbances being the most detrimental clinical phenotype in RTT (Smeets et al, 2012 ). Recent studies have evaluated the QOL in subjects with RTT and their caregivers using questionnaires such as the Italian version of the impact of childhood illness scale (Parisi et al, 2016 ). These studies have demonstrated a significant negative impact on both the child’s development and the entire family.…”
Section: Appendix Amentioning
confidence: 99%
“…Recent studies have evaluated the QOL in subjects with RTT and their caregivers using questionnaires such as the Italian version of the impact of childhood illness scale (Parisi et al, 2016 ). These studies have demonstrated a significant negative impact on both the child’s development and the entire family.…”
Section: Appendix Amentioning
confidence: 99%
“…Patients with RTT show cognitive deficits, which could be due to impairment in the synaptic functions [266268]. Synaptic functions were altered in the MeCP2 mutant mouse models, consistent with the structural and behavioural alterations [277279], thereby causing E/I imbalance.…”
Section: Gene Mutation In Intellectual Disability and Autistic Spectrmentioning
confidence: 78%
“…Studies have shown that approximately 1 in 10 000 females is affected by RTT [266][267][268]. Studies on human patients between 7 and 18 months of age showed phenotypes of deteriorated higher cognitive and social functions, stagnancy of brain development, severe dementia, autism, ataxia and repetitive hand movements [266][267][268]. Constitutive MeCP2 hemizygous KO and conditional KO mouse models showed motor deficits such as improper gait, hindlimb clasping, irregular breathing [98] and microcephaly [98,269], and did not survive for more than 12 weeks after birth.…”
Section: Behavioural Alterationsmentioning
confidence: 99%
“…Durante o levantamento bibliográfico foi possível observar que as pesquisas relacionadas à QV da população com DI, em sua maioria, tiveram como objetivos avaliar a QV referida pelas famílias da PcDI (KALAY et al, 2010;VAN GAMEREN-OOSTEROM et al, 2011;MORRISSE et al, 2013;PARISI et al, 2016) ou verificar a aplicabilidade e confiabilidade de protocolos (BREDEMEIER et al,, 2014;CANTORANI et al, 2015;. A QV dos atendentes pessoais de PCD's também foi avaliada em diversos estudos (JUHÁSOVÁ, 2015;PARISI et al, 2016). Foram encontrados poucos estudos investigando a QV referida pelo sujeito com DI e, alguns dos estudos encontrados, utilizaram entrevistas elaboradas pelos próprios pesquisadores (KALAY et al, 2010;EMERSON et.…”
Section: Qualidade De Vida Na Deficiência Intelectualunclassified